Balancing the Scales: Navigating Benefits and Risks in Indonesia's Sharia FinTech Landscape - Lubis, Hikmah Adelia Zuhri; Khairisma, Khairisma; Puspitaningrum, Rani; Ichsan, Ichsan (Journal of International Conference Proceedings, 2023)
This research provides a thorough literature analysis to clarify the dynamics of advancing financial technology that complies with Shariah for inclusive development and implementing broad surveillance in Indonesia. The objective is to provide a qualitative review of the current studies to offer insightful perspectives on the growth and risks related toÂ Shariah FinTech. This study integrates a library research approach with a qualitative research methodology. The literature results suggest that Shariah-compliant FinTech is being more widely used in Indonesia, demonstrating its advantages and disadvantages. This literature-based study advances our understanding of the complex balance needed for the ethical and sustainable development of Indonesia's developing Shariah FinTech sector.